Competitive two person zero-sum game with linear increment function - Dranseikienė, Jolanta; Sūdžiūtė, Daina (Lietuvos matematikos rinkinys, 2000)
We analyze the competition of two firms with increment function of the first firm c(x) = kx +1 an analogue to that in [1] with the increment c = 1. The optimal strategies X*, Y* and the value v of the game in explicit form are obtained, their parameters a, α, C0, C1 being the solutions of the equation system. The values of the game parameters for various k are presented in graphic form.